2021
DOI: 10.1053/j.gastro.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variation With Cirrhosis: A Multi-Trait Genome-Wide Association and Gene–Environment Interaction Study

Abstract: See Covering the Cover synopsis on page 1435. BACKGROUND & AIMS:In contrast to most other common diseases, few genetic variants have been identified that impact risk of cirrhosis. We aimed to identify new genetic variants that predispose to cirrhosis, to test whether such variants, aggregated into a polygenic score, enable genomic risk stratification, and to test whether alcohol intake or body mass index interacts with polygenic predisposition. METHODS: We conducted a multi-trait genome-wide association study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 57 publications
3
88
0
Order By: Relevance
“…( 22 ) These lean patients with NAFLD likely have a higher prevalence of common variants associated with NAFLD prevalence and severity. ( 23 ) The most well‐characterized common variant associated with NAFLD is the nonsynonymous variant p.I148M in the patatin‐like phospholipase domain containing 3 ( PNPLA3 ) gene, which has increased prevalence in Hispanics ( 24 ) and is associated with an increased risk of hepatic steatosis, ( 24 ) NASH, ( 25,26 ) cirrhosis, ( 27 ) and HCC. ( 28 ) Stender et al demonstrated that adiposity, assessed by BMI, amplifies the effect of this PNPLA3 polymorphism on fatty liver disease and its progression to cirrhosis; however, this finding was in a population of European ancestry.…”
Section: Common Genetic Variants and Nafld Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…( 22 ) These lean patients with NAFLD likely have a higher prevalence of common variants associated with NAFLD prevalence and severity. ( 23 ) The most well‐characterized common variant associated with NAFLD is the nonsynonymous variant p.I148M in the patatin‐like phospholipase domain containing 3 ( PNPLA3 ) gene, which has increased prevalence in Hispanics ( 24 ) and is associated with an increased risk of hepatic steatosis, ( 24 ) NASH, ( 25,26 ) cirrhosis, ( 27 ) and HCC. ( 28 ) Stender et al demonstrated that adiposity, assessed by BMI, amplifies the effect of this PNPLA3 polymorphism on fatty liver disease and its progression to cirrhosis; however, this finding was in a population of European ancestry.…”
Section: Common Genetic Variants and Nafld Riskmentioning
confidence: 99%
“…( 48 ) Recently, a polygenic risk score for cirrhosis incorporating 12 independent genetic variants was derived and validated. ( 27 ) Future efforts should evaluate whether lean patients with NAFLD have high polygenic risk score.…”
Section: Common Genetic Variants and Nafld Riskmentioning
confidence: 99%
“…[30][31][32][33] We are therefore presently moving to a model where, across the continuum of the distribution of the inherited predisposition to NAFLD in the population, the development of polygenic risk scores (PRS) can stratify the risk of this condition and of liver-related complications. 30,31,[34][35][36] For example, "high" PRS can predict the evolution to cirrhosis and HCC independently of classical risk factors in individuals with dysmetabolism and/or NAFLD, potentially being able to aid in the clinical management and in the design of referral pathways. 35 On the other hand, it has become clear that the main common risk variant and PRS cannot discriminate accurately between "metabolic" and "genetic" NAFLD.…”
Section: Role Of Genetic Determinantsmentioning
confidence: 99%
“…The sudden cardiac arrest-related gene variations were selected from GWAS results. To determine whether the polymorphisms of these SNPs are prone to induce SCD in the Chinese Han population, 21 SNPs with P<1x10 -7 were selected from GWAS, based solely on previous studies (22)(23)(24)(25). The results revealed that the 21 SNPs were independent and did not exhibit any linkage disequilibrium cluster.…”
Section: Construction Of a Multiplex Pcr Systemmentioning
confidence: 99%